Understanding Civil Engineering and Architectural Engineering Students’ Perceptions about BIM Practices - Fitriani, Heni; Yanti, Audrey Fitri; Foralisa, Mona; Muhtarom, Ahmad (Semarang State University, 2021)
The use of BIM within construction industry is experiencing development. However, the development of BIM in Indonesia is still very limited. One of the inhibiting factors in the development of BIM is the inadequate availability of BIM specialists and professionals in the construction industry so that an active role of students is needed as the main target in meeting the needs of the construction industry in Indonesia. This research was conducted to analyze the perceptions of students of the Sriwijaya University in the civil engineering and architecture study programs regarding perceptions of knowledge, benefits, adoption, and development of BIM. This study used a quantitative approach. Data collection was carried out using a questionnaire. It was stated that ‘BIM technology and concepts are important for students to learn’ was to be the highest rank with an average score of 4.70 for Civil Engineering and 4.56 for architecture students. The result shows that the benefits of BIM that influence the most in the construction industry are to improve the quality of construction and enhance design visualization. The most significant driving factor on the development and adoption of BIM is education and training on using BIM software. In addition, the most significant inhibiting factors that influence the development and adoption of BIM are lack of education or training on the use of BIM and lack of knowledge on how to implement BIM software.